Evolution of Aortic Wall Thickness and Stiffness With Atherosclerosis. Issue 5 (May 2015) - Liu, Chia-Ying; Chen, Doris; Bluemke, David A.; Wu, Colin O.; Teixido-Tura, Gisela; Chugh, Atul; Vasu, Sujethra; Lima, João A.C.; Hundley, W. Gregory
<x xml:space="preserve">Abstract</x> The study was performed to determine age, sex, and time-dependent changes in aortic wall thickness (AWT) and to evaluate cross-sectional associations between AWT and arterial stiffness in older adults. Three hundred seventy-one longitudinal and 426 cross-sectional measurements of AWT from cardiovascular magnetic resonance imaging studies conducted within the Multi-Ethnic Study of Atherosclerosis were analyzed at 2 points in time, in 2000 to 2002 and then again from follow-up examinations in 2010 to 2012. Aortic wall thickness was determined from a double inversion recovery black-blood fast spin-echo sequence, and aortic stiffness was measured from a phase-contrast cine gradient echo sequence. The thickness of the midthoracic descending aortic wall was measured and correlated to distensibility of the ascending aorta and aortic pulse wave velocity. The average rate of AWT change was 0.032 mm/y. The increase in AWT was greater for those aged 45 to 54 years relative to individuals older than 55 years (P trend<0.001). Ascending aortic distensibility was lower (P<0.001) and pulse wave velocity was higher (P=0.012) for hypertensive subjects. After adjustment for traditional risk factors, distensibility of the ascending aorta was significantly related to AWT in participants without hypertension. Hypertension was associated with increased aortic stiffness independent of aortic wall thickness.